Mutu Layanan Pendidikan di SMP Assa’adah Kecamatan Duren Sawit Jakarta Timur - Nukman, Muhammad; Supadi, Supadi; Zulaikha, Siti (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2017)
The research was conducted in Assa’adah Junior High School District Duren Sawit East Jakarta, which aims to identify and obtain an overview of the quality of educational services. This research was conducted in October 2016 until February 2017. approach used is qualitative approach with methods descriptions. Data collection was done through interviews, observation and documentation. source data from this study is the principal and several supporting informant as deputy principals and heads of administration. Based on the results of research and data analysis, it can be concluded that the quality of service at Assa’adah Junior High School has been running well. then, from the quality of the services performed directly supervised by the principal. it can be seen from the quality planning services starting from problem analysis, identification of needs, formulation of objectives, devise alternative actions, action selection, preparation of work plans, implementation of the work plan, evaluation, and feedback. Furthermore, quality control process of comparing the performance of the service begins with the target of evaluation, problem analysis, and manufacture of alternative actions. then, the strategy of increasing the quality of services consisting of the development of educators, improved quality of service, and continuous improvement.